New media literacy, self-acceptance, and psychological flexibility in enhancing Gen Z wellbeing - Lim, Jia Hang; Ahmad, Mahadir Bin; Prihadi, Kususanto Ditto (Psychology, Society & Education, 2024)
Despite the growing interest in psychological wellbeing among Generation Z (born 1997-2012), there is a gap in understanding how new media literacy, unconditional self-acceptance, and psychological flexibility interact to influence psychological wellbeing, particularly in the context of the digital age. The proliferation of digital technologies has reshaped the way Generation Z interacts with the world, influencing various aspects of their mental health and psychological wellbeing. This study was conducted to explore whether new media literacy moderate the mediation effect of unconditional self-acceptance on the relationship between psychological flexibility and psychological wellbeing. A total of 240 university students from Malaysia aged 18-25 were recruited using purposive sampling method. Results showed that psychological flexibility directly and significantly enhances psychological wellbeing regardless of an individual’s level of new media literacy. Furthermore, the contribution of psychological flexibility on psychological wellbeing is significant through unconditional self-acceptance among individuals with low and moderate levels of new media literacy. This study reveals that new media literacy enhances the effectiveness of psychological flexibility in promoting psychological well-being among Generation Z, suggesting that new media literacy is crucial for resilience and well-being in the digital age, particularly during identity development.